Compliance of Culinary Business Operators with Halal Certification Regulations: A Study of Street Food Vendors in Somba Opu District, Gowa Regency - Nashrullah Hidir; Muhammad Zul Ikram Safei; Rahmawati Muin; Rahman Ambo Masse (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the compliance of culinary business operators with halal certification regulations among street food vendors in Somba Opu District, Gowa Regency. The research focuses on the effectiveness of government literacy and educational inclusion programs, the level of vendors’ understanding and access to certification obligations, the implementation of compliance throughout the production–distribution–sales chain, and the supporting and inhibiting factors affecting compliance. This study employs a qualitative approach using a phenomenological method. Data were collected through in-depth interviews, non-participant observations, and documentation involving ten street food vendors and three key informants from the Halal Product Assurance Organizing Agency (BPJPH). Data analysis was conducted using the interactive model developed by Miles and Huberman. The findings indicate that the level of compliance remains low, both administratively and substantively. Literacy and inclusion programs, such as the Free Halal Certification Program (SEHATI) and the SIHALAL digital system, have not yet optimally reached their target groups due to digital literacy gaps, limited direct technical assistance, and perceptions of procedural complexity. Vendors’ understanding of halal certification remains normative and intuitive and has not yet met the procedural accountability standards required by the Halal Product Assurance System (SJPH). The main supporting factors include religious awareness, market pressure, and affirmative government programs, while the inhibiting factors consist of limited digital infrastructure, bureaucratic complexity, and regulatory uncertainty. This study concludes that improving compliance requires a shift from a compliance-driven approach toward an enablement-driven approach through procedural simplification, strengthened field assistance, and the development of inclusive service designs. Such an approach is consistent with the Islamic principles of taysir (facilitation) and maqashid al-shariah (the objectives of Islamic law).